Age as a major factor in the onset of multiple populations in stellar clusters - Martocchia, Silvia; Cordero, Maria J. (Monthly notices of the Royal Astronomical Society, 2018)
Abstract. It is now well established that globular clusters (GCs) exhibit star-to-star light-element abundance variations (known as multiple populations, MPs).